Diversity of root-knot nematodes associated with tubers of yam (Dioscorea spp.) established using isozyme analysis and mitochondrial DNA-based identification - Kolombia, Y.A.; Karssen, G.; Viaene, N.; Kumar, P. Lava; Sutter, N. de; Joos, L.; Coyne, Danny L.; Bert, W. (2017)
The root-knot nematodes (RKN), Meloidogyne spp., represent an important threat to yam (Dioscorea spp.) production in West Africa. With the aim to establish the diversity of RKN species affecting yam tubers, for control and resistance screening purposes, surveys were conducted in the main yam producing areas of Nigeria. Galled tubers (N = 48) were collected from farmers’ stores and markets in nine states in Nigeria and in one district in Ghana. RKN isolated from yam tubers were identified using enzyme phenotyping (esterase and malate dehydrogenase) and mitochondrial DNA (mtDNA) NADH dehydrogenase subunit 5 (Nad5) barcoding.